Distributed Bragg reflector fibre laser‐based sensor array for multi‐parameter detection. Issue 18 (1st August 2014) - Yu, Kuanglu; Wu, Chongqing; Mao, Yaya; Wang, Zhi; Lu, Chao; Tam, Hwa‐Yaw; Zhao, Yao
Abstract : A sensor array employing the distributed Bragg reflector (DBR) fibre laser is presented. This array could be utilised as a multi‐channel multi‐functional detector for bending radius, transverse load and axial strain by simultaneously monitoring the lasing wavelength and the output beat note frequency. The measurement theory of the DBR fibre laser is explained, and it is then experimentally verified with a three‐probe array. The system's detection sensitivities for curvature, transverse load and axial strain are found to be 600 MHz/cm −2, 1.3 MHz/g and 1.263 pm/με, respectively.